Finite element analysis of reinforced concrete frame by using ANSYS - Phang, Sze Qian (2019)
In this research, a multi-storey building has been analysed by using ANSYS software.This research is to determine the strain, stress, maximum deflection, deformation and also checking the structure according to Eurocode 2. Major of the buildings constructed in Malaysia are reinforced concrete buildings compared to steel frame buildings. Reinforced concrete structure design software is very important to help civil engineers in finite element analysis. The type of material and the geometry for the structure was satisfied in cases it passed all the designing for tensile, buckling and compression. The values for the input variables are generated randomly by using Monte Carlo Simulation with given mean values and standard deviation or as prescribed samples using Response Surface Method. From the result of simulation, we can know the behaviour of the reinforced concrete structure under the input parameter that applied. Then, from the probabilistic analysis, we collect the result of cumulative distribution function, the histogram plot for input and output parameter, sensitivity plot and simple history plot for all parameter.